Who Is Getting Nuked? Nuclear Taboo, Adversary Types, and Atomic Dispositions. (1st January 2023) - Joshi, Yogesh
Abstract: Janina Dill, Scott Sagan and Benjamin Valentino have demonstrated how calculations over the morality of contending norms may influence public's readiness to use nuclear weapons. I argue that such atomic dispositions are highly contingent on the nature of the adversary. Public may react differently to various nuclear targets because adversaries evoke different levels of retributiveness. When deciding between the lives of fellow citizens and those of foreign noncombatants, a bargain is easier to reach against targets which evoke feelings of hatred and anger due to historical, cultural or domestic political reasons. Using the Indian case, I demonstrate why the variance in the character of the threat is a substantive issue. Specifically, I show why the India-China dyad exhibits a greater degree of normative prohibition compared to the India-Pakistan dyad.